A Cross-Sectional Study Comparing Two Opt-Out HIV Testing Strategies in the Out-Patient Setting - Greta Tam; Samuel Yeung Shan Wong (Frontiers Media S.A., 2021)
Background: HIV infections are generally asymptomatic, leading to undetected infections and late-stage diagnoses. There are a lack of acceptable testing strategies for routine opt-out HIV screening. Our aim was to evaluate and compare the diagnostic yield of routine opt-out HIV testing strategies in two out-patient settings in a low HIV prevalence country: The public primary care and specialist out-patient care settingMethods: A cross-sectional study was conducted in a primary care clinic over a four-week period in 2016 to 2017 and in a specialist out-patient clinic over a concurrent 11-month period. Patients were invited to complete a questionnaire assessing demographic characteristics, acceptance of opt-out HIV testing as a policy in all out-patient clinics in Hong Kong and reasons if refusing the HIV test. All respondents were offered an HIV test.Results: This study included 648 and 1,603 patients in the primary care and specialist out-patient clinic, respectively. Test acceptability was 86 and 87% in the primary care and specialist out-patient setting, respectively. Test uptake was 35 and 68% in the primary care and specialist out-patient setting, respectively. No HIV infections were detected.Conclusion: Opt-out HIV testing during routine blood taking in the specialist out-patient setting achieved a high test uptake and acceptability. In contrast, opt-out HIV testing using rapid finger-prick tests in the primary care setting was not effective.